POTATO SEED PRODUCTION IN RUSSIA - Anisimov, Boris (Potato Journal, 2019)
Potato J (2018) 45 (2): 152-158POTATO SEED PRODUCTION IN RUSSIAB Anisimov1, E Simakov1, A Mityushkin1, A Zhuravlev1, E Blinkov1 and K Arshin1ABSTRACT: Detailed knowledge of the actual problems of production of seed potatoes is extremely important for the development of the Russian and nternational potato market in general. The authors propose special phytosanitaryrequirements to the virus and bacterial diseases of potato that are to be obeyed within the selected potato seed production zones. A special attention is devoted to the cultural practices helping to reduce exposure of infections and minimize theirspread via control of vectors. This paper presents the information regarding seed potato quality improvement in Russia.